Automotive emission abatement: studies on the effect of Tio2-co based catalytic converter / Ku Halim Ku Hamid and Muhd. Hairul Azman Abas - Ku Hamid, Ku Halim; Abas, Muhd. Hairul Azman (2002)
Emissions from automotive exhausts can be reduced by catalytic converters located in the exhaust system. Automobile exhaust converters were introduced in 1975 to oxidize the unburned CO and HC to carbon dioxide (CO2) and water (H2O) respectively. A second-generation converter was introduced in the U.S. in 1981 which catalyzed the oxidation reactions and simultaneously reduced nitrogen oxides to nitrogen. These three-way converters (TWC) have been used in all new vehicles since then. A newly designed catalytic converter system was established in this study to investigate the effectiveness of the catalytic reaction. Pieces of stainless steel wire mesh supported with Co/TiO2 were arranged linearly inside the exhaust chamber to increase the reaction area of the gases to catalytically transform into relatively benign ones. The wire mesh was rearranged in order to replace the role of conventional ceramic honeycomb monolith, which made of cordierite and coated with washcoat to support the catalytic material. Application of the stainless steel wire mesh as a basic design could provide a low cost and competitive catalytic material supporter. Each pieces was placed closed to each other before it was impregnated with TiO2 and Cobalt. The effectiveness of the catalyst was determined by analyzing the exhaust emission before and after it was passed through the cat-co. The result shows that the amount of toxic gases level in the exhaust emission decreased as closed to the commercial cat-co capacity.